The ginger polyphenol 6-gingerol elicits minimal changes in an ex vivo human gut microbiome - Mahalak, Karley K.; Narrowe, Adrienne B.; Firrman, Jenni; Lemons, Johanna M. S.; Liu, LinShu (Frontiers in Nutrition, 2026)
Ginger (Zingiber officinale) has a long history of use in traditional medicine and the modern world to alleviate health conditions, particularly those related to indigestion and nausea. Gingerols are phenolic bioactive compounds found in ginger. It has been suggested that health benefits associated with gingerols may be due to modification of the gut microbiome, especially in disease models. However, the impact of gingerol on a healthy human gut microbiome, and whether age affects gingerol activity, is not well understood. To address this, the impact of 6-gingerol, the most abundant polyphenol found in ginger, on the gut microbiomes of four age groups (infants, children, adults (22–40), and adults (60+)) was determined using SIFR® technology. Following a 24-h incubation with 6-gingerol, microbial community genomic analysis was performed together with metabolic analysis to determine the impact of 6-gingerol on the gut microbiota ex vivo. Using this method, 6-gingerol was determined to have no significant impact on the gut microbiota in terms of community density, community diversity, or short-chain fatty acid production. This study found that, in healthy gut microbiota, 6-gingerol did not have a strong effect within a 24-h period of treatment.